Incidence of prolonged transitional neonatal hypoglycemia and associated factors among neonatal admissions in South Gondar public hospitals, North-Central Ethiopia: a prospective cross-sectional study - Solomon Demis Kebede; Tigabu Munye Aytenew; Kindu Agmas; Worku Necho Asferie; Natnael Moges (Frontiers Media S.A., 2024)
BackgroundUnlike in developed countries, neonatal morbidity and mortality are the leading challenges associated with easily preventable and treatable disorders during the neonatal period in low- and middle-income countries. However, evidence-based data about prolonged transitional hypoglycemia and associated factors are highly limited in Ethiopia and resource-limited countries.MethodsAn institution-based prospective cross-sectional study was conducted at public hospitals in South Gondar in neonatal intensive care units (NICUs). The data were entered and analyzed using SPSS version 23. Descriptive statistics were used to summarize maternal characteristics. Multivariate binary logistic regression at a p value <0.05 was used.ResultsA total of 400 neonates, admitted to NICUs in public hospitals within 48-72 h of birth between October 2, 2021, and June 30, 2022, were included in the study. The incidence of prolonged transitional neonatal hypoglycemia (PTHG) was 23.5% (19.3%-28%). The factors associated with PTHG were hypothermia (AOR = 4.41; 95% CI = 2.72-10.92), preterm birth (AOR = 3.5; 95% CI = 1.69-11.97), perinatal asphyxia (AOR = 2.5; 95% CI = 1.34-9.67), and pathological jaundice (AOR = 2.3; 95% CI = 1.21-10.34). In contrast, spontaneous vaginal delivery (SVD) was a protective factor (AOR = 0.72; 95% CI = 0.35-0.88).ConclusionsThe incidence of (PTHG) was nearly one-fifth. Factors increasing the risk of PTHG were hypothermia, preterm birth, perinatal asphyxia (PNA), early onset of sepsis (EONS), and pathological jaundice. Spontaneous vaginal delivery (SVD) was also a protective factor. Preventing neonatal hypothermia was the main measure used to reduce PTHG in the study area. Special attention could be given to neonates with prematurity, early onset neonatal sepsis (EONS), birth asphyxia, and pathological jaundice, as monitoring their RBS could lead to a significant change in reducing PTHG.